The reformation encounter: Martin Luther's assessment of Islam and the Turks in the aftermath of Constantinople's fall - Jalal Nori, Abdulwahed; Sidiq, Sarkawt Tawfeeq (IIUM Press, 2024)
After Muhammad II captured Constantinople in 1453 and ended the Byzantine Empire, Islam began to spread to Europe over the next century. It was this constant threat that led Martin Luther (1483–1546) to become acquainted with Islam and acquire information about the Turks and Muslims. Luther was the pioneer of the 16th century’s Reformation in Europe and the founder of the Protestant movement. Luther’s assessment of Islam and the Turks are investigated in this article with the questions of main themes and subsequent theses. It was observed that Luther used an exclusionary, judgmental, and reactive language on Islam and Turks. His assessments are in compliance with the thesis that was constructed by Christians in Medieval Europe, with the exception of picturing Turks as papist, and his opposite attitudes against the Crusades. The article found conclusively that Luther was highly affected by his own theological and political positions, as well as the political developments of his period.